Field evaluation of durum wheat landraces for prevailing abiotic and biotic stresses in highland rainfed regions of Iran - Reza Mohammadi (Crop Journal, 2015)
Biotic and abiotic stresses are major limiting factors for high crop productivity worldwide. A landrace collection consisting of 380 durum wheat (Triticum turgidum L. var. durum) entries originating in several countries along with four check varieties were evaluated for biotic stresses: yellow rust (Puccinia striiformis Westendorf f. sp. tritici) and wheat stem sawfly (WSS) Cephus cinctus Norton (Hymenoptera: Cephidae), and abiotic stresses: cold and drought. The main objectives were to (i) quantify phenotypic diversity and identify variation in the durum wheat landraces for the different stresses and (ii) characterize the agronomic profiles of landraces in reaction to the stresses. Significant changes in reactions of landraces to stresses were observed. Landraces resistant to each stress were identified and agronomically characterized. Percentage reduction due to the stresses varied from 11.4% (yellow rust) to 21.6% (cold stress) for 1000-kernel weight (TKW) and from 19.9 (yellow rust) to 91.9% (cold stress) for grain yield. Landraces from Asia and Europe showed enhanced genetic potential for both grain yield and cold tolerance under highland rainfed conditions of Iran. The findings showed that TKW and yield productivity could be used to assess the response of durum wheat landraces to different stresses. In conclusion, landraces showed high levels of resistance to both biotic and abiotic stresses, and selected landraces can serve in durum wheat breeding for adaptation to cold and drought-prone environments.